MANAGEMENT PLAN OF PROGAMME DESA MANDIRI CINTA PETANI (SARI TANI) IN TIMOR TENGAH UTARA REGENCY - Sulistio Diliwanto Binsasi (Sean Institute, 2023)
This research is intended to analyze the management planning of the Independent Village Love Farmer Program (Sari Tani) in North Central Timor District. The problems in this study are how to plan the management of the Independent Village Love Farmers Program (Sari Tani) in North Central Timor District and what factors hinder and support the management planning of the Independent Village Love Farmers Program (Sari Tani) in North Central Timor District . The purpose of this study was to obtain an overview of the management planning for the Sari Tani program in North Central Timor District. The methods used to collect data are observation and interviews using qualitative descriptive data analysis techniques. After the researcher displays the empirical data found at the research location. The results of the research found that the management planning for the Sari Tani program had not been maximized, namely: the village government and the community had not been accommodated in planning the Sari Tani program at the village level so that the planning was of poor quality, did not identify the potential for superior products at the village level to be developed through the Sari Tani program, there was no rules of sanctions for beneficiaries who do not return the revolving capital of the Sari Tani program in technical guidelines, delays in returning Sari Tani funds, community behavior that is apathetic, lazy and only looking for opportunities to get assistance, lack of human resources, socio-cultural conditions and inadequate levels of education very influential on the implementation of the program.